Therapeutic strategy for patients with bleeding rectal varices complicating liver cirrhosis. Issue 11 (7th January 2014) - Yoshino, Kiyoko; Imai, Yukinori; Nakazawa, Manabu; Chikayama, Taku; Ando, Satsuki; Sugawara, Kayoko; Hamaoka, Kazuhiro; Inao, Mie; Oka, Masashi; Mochida, Satoshi
<x xml:space="preserve">Abstract</x> Aim Although rupture of rectal varices is rarely encountered, it may provoke massive and fatal hemorrhage in patients with liver cirrhosis. We examined the clinical features of patients showing bleeding from rectal varices to establish a suitable therapeutic strategy for the lesions. Methods Twelve cirrhotic patients with bleeding rectal varices were enrolled. Surgical suture, endoscopic variceal ligation (EVL) or balloon tamponade was performed to achieve the initial hemostasis. Then, the feeding and drainage vessels of the varices were evaluated by computed tomography, and additional procedures were undertaken: EVL was performed when the sizes of the varices and feeding vessels were small. In contrast, in patients with varices of large sizes, balloon‐occluded retrograde transvenous obliteration (B‐RTO) was performed when single or two drainage vessels were identified, while endoscopic injection sclerotherapy (EIS) using ethanolamine oleate was carried out for varices with three or more drainage vessels. Results The Child–Pugh class was grade A in four, B in six and C in two patients. Eleven patients had received previous therapy for esophageal varices. Initial hemostasis was achieved by surgical suture in three patients, EVL in one patient and balloon tamponade in two patients. EVL, EIS and B‐RTO were carried out as additional procedures in seven, three and one patient, respectively. Rebleeding from the rectal varices occurred in only one patient who underwent EVL as an additional procedure. Conclusion Bleeding from rectal varices was controlled satisfactorily by the therapeutic strategy of selecting EVL, EIS or B‐RTO as an additional therapy according to the size and hemodynamics of the varices.